Prediction of Fluorooxoborates with Colossal Second Harmonic Generation (SHG) Coefficients and Extremely Wide Band Gaps: Towards Modulating Properties by Tuning the BO3/BO3F Ratio in Layers - Zhang, Bingbing; Tikhonov, Evgenii; Xie, Congwei; Yang, Zhihua; Pan, Shilie (Angewandte Chemie International Edition, 2019)
Fluorooxoborates have inspired investigations of deep‐ultraviolet (DUV) nonlinear optical (NLO) materials that can meet the multiple criteria. Herein, five stable structures with the composition of BaB2O3F2 (I–V) are discovered using the ab initio evolutionary algorithm. Among them, BaB2O3F2‐I has been synthesized experimentally and confirms the reliability of the method. All of the predicted structures possess extremely wide band gaps (8.1–9.0 eV). Moreover, four new structures exhibit giant second harmonic generation (SHG) coefficients (>3×KDP, d36=0.39 pm V−1). A novel type of the [BOF] layer with BO3:BO3F ratio of [1:1] is found in BaB2O3F2‐II and BaB2O3F2‐III. While BaB2O3F2‐IV and BaB2O3F2‐V are solely composed of the BO3F group and have colossal SHG coefficients (ca. 4×KDP). It gives the direct evidence that the BO3F group could generate strong SHG effect. Most importantly, the influences of BO3:BO3F ratio and their number density on band gap, birefringence and SHG effects are investigated. Fluorooxoborates have inspired investigations of deep‐ultraviolet (DUV) nonlinear optical (NLO) materials. Five stable structures with the composition of BaB2O3F2 (I–V) are discovered using the ab initio evolutionary algorithm. Among them, BaB2O3F2‐I is known and confirms the reliability of the method. It shows that BO3F groups can give large band gaps and strong second harmonic generation (SHG) responses.